2016
DOI: 10.1073/pnas.1600813113
|View full text |Cite
|
Sign up to set email alerts
|

MEKK2 mediates an alternative β-catenin pathway that promotes bone formation

Abstract: Proper tuning of β-catenin activity in osteoblasts is required for bone homeostasis, because both increased and decreased β-catenin activity have pathologic consequences. In the classical pathway for β-catenin activation, stimulation with WNT ligands suppresses constitutive phosphorylation of β-catenin by glycogen synthase kinase 3β, preventing β-catenin ubiquitination and proteasomal degradation. Here, we have found that mitogen-activated protein kinase kinase kinase 2 (MAP3K2 or MEKK2) mediates an alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…Next, we asked whether activation of MEKK2 and MEKK3 at physiological condition is able to inhibit Hh pathway activity. FGF2 has been shown to activate MEKK2 in osteoblasts [ 24 ]. Interestingly, FGF2 blocks Shh signaling in neuronal precursors and tumor cells [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we asked whether activation of MEKK2 and MEKK3 at physiological condition is able to inhibit Hh pathway activity. FGF2 has been shown to activate MEKK2 in osteoblasts [ 24 ]. Interestingly, FGF2 blocks Shh signaling in neuronal precursors and tumor cells [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis was performed according to a previously described standard protocol. 49 Primary antibodies were specific for SLIT3 (1:500; R&D Systems, AF3629), ROBO1 (1:500; Abcam, ab7279), ROBO2 (1:1000; Abcam, ab75014), YAP (1:1,000; Cell Signaling, 4912), p-YAP (1:1,000; Cell signaling, 4911), AKT (1:1,000; Cell Signaling, 4691), p-AKT (1:1,000; Cell Signaling, 4060), ERK (1:1,000; Cell Signaling, 9102), p-ERK (1:1,000; Cell Signaling, 9101) and beta-actin (1:5,000; sc-47778, Santa Cruz) or Hsp90 (1:1000; sc-13119, Santa Cruz). Secondary anti-mouse/rabbit HRP-conjugated antibodies were subsequently applied.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been reported that Cdh1, another ubiquitination-related molecule that could also augment Smurf1 activity 18 19 , rather than CKIP-1 has a pivotal role in regulating the MEKK-2 pathway. Moreover, another recent study observed the unaltered BMP response in Mekk2 gene-depleted osteoblasts and demonstrated that MEKK-2 is dispensable for noncanonical BMP-JNK pathway activation in osteoblasts 20 . Thus, we focused on the CKIP-1-mediated ubiquitination regulation of Smad-dependent BMP signaling within osteoblasts during the development of GIO.…”
Section: Discussionmentioning
confidence: 95%